Escolas promotoras de saúde na América Latina: uma revisão integrativa da literatura - Faria, Flávia Amélia Costa (2010)
The modernization of the health concept culminated in the proposal for Healthy Public Policy, in which one of the most important is the Initiative for Healthy Cities, where the government and civil society develop projects for the citizens who live in communities, through actions at different places, including schools. These actions contribute to building healthy environments. It is conception that builds the concept of Health Promoting Schools - a place that values healthy living among students, families and communities, as well as their life skills. The Health Promoting School can be regarded as a key strategy for the implementation of healthy city, from the perspective of inclusion and participation, since starring in the action can change the frame of the unfavorable conditions of life. PURPOSE: Conduct an integrative literature review resulting in reported experiences of the Health Promoting Schools in Latin America and the Caribbean; identify the concepts of health promotion and Health Promoting Schools, as well as actions related to health promotion present in these articles. METHODS: It was made an integrative literature review, using the LILACS database. For search of articles have proposed two strategies, A and B, where they were recovered over a thousand abstracts relating to the subject and of which only eight items constituted the final sample bibliography. RESULTS: Sample articles literature responded to our inclusion criteria and our objectives, however, demonstrated that there is a striking feature in the proposed hygienic health for schools, which limit the actions of health promotion and impede the expansion of Health Promoting School. CONCLUSION: The Health Promoting Schools can be considered an option to improve quality of life of an entire community, since they propose projects and actions that promote the school population and its environment. If well executed, the shares should be shared with the countries of the Latin American Network of Health Promoting Schools and will be responsible for training and critical citizens aware of their personal skills.